Stress Management for Family and Community During the COVID-19 Pandemic - Suryati, Eti; Umar, Erna; Hamdiah, Dedeh (KnE Life Sciences, 2021)
Although mental health issues are not considered as a disorder that causes immediate death, this disorder can lead to an individual’s inability to work. Stress is experienced by everyone. Mental pressure if not managed properly can lead to mental disorders and despair (suicide). For this reason, management of stress is an important thing in human life. A total of 30 community members agreed to participate in this program. Most (80%) were women with a mean age of 32.54 (SD = 2.76). The most frequently used sources of information were mostly (86.7%) via the internet. Based on the results of the paired t-test, it was found that this program was effective in increasing knowledge, attitudes, and behavior about COVID-19 and stress (p value <0.001), with a difference value of 7.13 for knowledge, 5.02 for attitudes, and 4.24. for behavior, 3.45 for stress. This program is an approach based on the empowerment of health workers by utilizing existing applications for communication, namely social media and reminder systems. A subsequent program needs to be developed to increase the sustainability of this iniative, such as through integrated development and using technology as a medium of delivery and promotion. Keywords: stress management, COVID-19